Human and robot: an amity not a discord - Santok, Glen Denmer R.; Raheem, Ali Abdel; Chang, Ki Don; Rha, Koon Ho (Translational Andrology and Urology; Vol 6, No 2 (April 29, 2017): Translational Andrology and Urology (Global Urology), 2017)
Since the use of robot-assisted laparoscopic prostatectomy (RALP) was first reported in 2000, there has been rapid adoption of robotic surgery for men with prostate cancer (PCa). In the USA, more than 85% of prostatectomies are done robotically over open, and although the proportion is lower in the UK and Europe, it is increasing (1). Despite the cost and inherent minimally invasive advantage of the former over the latter this has gone exponential application without a strong evidence of benefit overcoming the costs. Recently, Yaxley et al. (2), has disclosed that the early outcomes of a well conducted prospective randomized trial. This has become a ringing bell, which triggered a lot of discussion about the flaws and strengths of this revelation in the field of urology. This study included of men with localized PCa who were electronically randomized to receive robot assisted radical prostatectomy (RARP) or open radical prostatectomy (ORP). The surgery was performed by a young robotic surgeon with 200-case and an experienced open surgeon with 1,500 cases. The primary endpoints were sexual and urinary function at 6 weeks, 12 weeks, and 24 months and oncological outcome. Their results showed that urinary and sexual function did not significantly differ at 12 weeks (83.80 vs. 82.50; P=0.48 and 35.00 vs. 38.90; P=0.18, respectively). However, RARP took the edge on the surgery time, occurrence of intraoperative adverse event, blood loss and length of hospital days (P